Investigation of seawater mineral promoted pyrolysis at low temperature for improving the adsorption capabilities of biochar. (April 2022) - Wen, Qin; Wang, Shihan; Liu, Sen; Li, Jihui; Chen, Yijia; Yang, Run; Xu, Shuying
Abstract: Naturally abundant seawater mineral was employed to engineer banana pseudostem and bamboo biochars through pyrolysis at different low temperatures for improving their adsorption capabilities for methylene blue (MB) and tetracycline (TC). The adsorption capabilities were greatly enhanced as the biochars were pyrolyzed at 300 °C with 50/1 (mL/g) dosage of seawater to biomass. For instance, the engineered banana pseudostem biochar exhibited 8.00 and 6.54 times higher adsorption capabilities than the corresponding pristine biochar for MB (447.79 mg/g vs 55.96 mg/g) and TC (100.59 mg/g vs 16.75 mg/g) at 25 °C, respectively. The characterization results indicated that a large number of carboxylates, lactone acid salts, and alkoxides were generated on the engineered biochar and a high cation exchange capacity was gained. The adsorption of MB was mainly attributed to cation exchange complying with hydrogen bonding and electrostatic interaction, whereas the adsorption of TC was realized by hydrogen bonding and complexation. Graphical abstract: Image 1 Highlights: Oxygen containing groups were regulated by seawater mineral-promoted pyrolysis. Carboxylates, lactonic salts and alkoxides were massively generated. High cation exchange capacity was obtained. High adsorption capabilities were achieved for methylene blue and tetracycline.